Trends in Functional Programming 14th International Symposium, TFP 2013, Provo, UT, USA, May 14-16, 2013, Revised Selected Papers - McCarthy, Jay.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes the thoroughly refereed revised selected papers of the 14th International Symposium on Trends in Functional Programming, TFP 2013, held in Provo, UT, USA in May 2013. The 10 revised full papers included in this volume were carefully and selected from 27 submissions. They cover topics such as distributed systems, education, functional language implementation, hardware synthesis, static analysis, testing, and total programming.
Keywords: Computer science; Logic design; Computer Science; Programming Techniques; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs